Pengaruh Service Quality dan Guest Experience terhadap Guest Loyalty dengan Variabel Guest Satisfaction Sebagai Mediasi di Plataran Canggu - Pradnyanata Adhi Dharma, I Gede; Putu Irma Yunita (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the effect of service quality and guest experience on guest loyalty with guest satisfaction as a mediating variable at Plataran Canggu. The research method used is a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 377 respondents who were guests of Plataran Canggu and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that service quality has a positive and significant effect on guest loyalty, while guest experience does not have a significant direct effect on guest loyalty. Furthermore, both service quality and guest experience have a positive and significant effect on guest satisfaction, and guest satisfaction has a strong positive effect on guest loyalty. In addition, guest satisfaction significantly mediates the relationship between service quality and guest experience with guest loyalty. The conclusion of this study confirms that guest satisfaction plays a crucial role in strengthening the relationship between service quality, guest experience, and guest loyalty at Plataran Canggu.   Keywords: Service Quality, Guest Experience, Guest Satisfaction, Guest Loyalty, Hospitality